Genetics of the taste receptor T2R38 correlates with chronic rhinosinusitis necessitating surgical intervention. Issue 3 (16th January 2013) - Adappa, Nithin D.; Howland, Timothy J.; Palmer, James N.; Kennedy, David W.; Doghramji, Laurel; Lysenko, Anna; Reed, Danielle R.; Lee, Robert J.; Cohen, Noam A.
<x xml:space="preserve">Abstract</x> Background We recently demonstrated the bitter taste receptor T2R38 upregulates sinonasal mucosal innate defense in response to gram‐negative quorum‐sensing molecules through increased nitric oxide production and mucociliary clearance. T2R38 was initially identified in the quest to understand the variability in bitter taste perception to the compound phenylthiocarbamide (PTC) and demonstrated to have polymorphisms generating diplotypes dividing people into PTC supertasters, heterozygotes (with variable PTC detection), and nontasters. We have further demonstrated that sinonasal epithelial cultures derived from supertasters significantly increase innate defenses in response to gram‐negative quorum‐sensing molecules compared with sinonasal cultures derived from heterozygotes and nontaster individuals. Based on this data, we hypothesize that supertasters are less likely to require sinus surgery compared with heterozygous or nontasters and that supertasters have improved surgical outcomes. Methods Banked sinonasal tissue samples from patients who had undergone primary functional endoscopic sinus surgery at the University of Pennsylvania or the Philadelphia Veterans Affairs Medical Center were genotyped for T2R38 and compared to the expected population distribution. Necessity for additional antibiotic therapy following the postoperative healing time frame was evaluated. Results A total of 28 patients were included in the study. Only 1 supertaster was identified (expected 5.6, p < 0.043). Additionally, 14 heterozygous and 13 nontaster patients were identified. Conclusion This pilot study investigating the genetics of the bitter taste receptor T2R38 in the context of primary sinonasal surgery demonstrates supertaster patients are less likely to need surgical intervention for chronic rhinosinusitis. Additional study is necessary to ascertain postsurgical outcomes.